Prevalence of Type II diabetes with reference to ageing and gender differences - K. Kanagalakshmi Vivekanandan (Journal of Research in Biology, 2016)
Diabetes, commonly referred as diabetes mellitus, in general describes a group of metabolic diseases that are caused by insulin deficiency. In which the person has high blood glucose level (blood sugar), either due to the insufficient production of insulin, or due to the body’s cells does not respond to insulin, or both. As long as the cells cannot take up the available glucose molecules from the blood of patients due to the lack of insulin hormone, it develops the sense of hunger (polyphagia). Kidneys act as a filter and normally reabsorb the blood glucose before it gets excreted in the urine, but when glucose level is high, kidnies cannot reabsorb all of the sugar, hence the excess sugar is dumped into the urine (polyurea). The increased urine production and consequential dehydration leads to the extreme thirst (polydipsia). India being the capital for diabetic world, visible increase of Type 2 diabetes is coupled with increasing age and that imposes a significant burden on the health care system. Hence, this work was therefore designed to assess the gender and age prevalence of type 2 diabetes mellitus (T2DM) patients attending Government Stanley Hospital, Chennai.